2001
DOI: 10.1073/pnas.98.4.1912
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological disruption of neurokinin 1 receptor function decreases anxiety-related behaviors and increases serotonergic function

Abstract: Alterations in serotonin (5-hydroxytriptamine, 5-HT), norepinephrine, and ␥-aminobutyric acid have been linked to the pathophysiology of anxiety and depression, and medications that modulate these neurotransmitters are widely used to treat mood disorders. Recently, the neuropeptide substance P (SP) and its receptor, the neurokinin 1 receptor (NK1R), have been proposed as possible targets for new antidepressant and anxiolytic therapies. However, animal and human studies have so far failed to provide a clear con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
130
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(146 citation statements)
references
References 39 publications
10
130
0
2
Order By: Relevance
“…Moreover, NK1 antagonists (eg MK-869, L-733060) have been shown preclinically to exhibit anxiolytic-like effects in gerbils in several different animal models including the elevated plus maze, fear conditioning, social interaction, and shock-induced foot tapping (Ballard et al, 2001;File et al, 2001;Gentsch et al, 2002;Rupniak et al, 2003;Varty et al, 2002b); and more recently, antidepressant-like effects in the tail suspension test (Varty et al, 2003). Consistent with these reports, genetic deletion of the NK1 receptor in mice resulted in anxiolytic and antidepressant effects in the elevated plus maze, novelty suppressed feeding model and the FST (Santarelli et al, 2001;Rupniak et al, 2001), providing additional support for the hypothesis that the NK1 receptor may be an important target for antidepressant/anxiolytic therapy.…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, NK1 antagonists (eg MK-869, L-733060) have been shown preclinically to exhibit anxiolytic-like effects in gerbils in several different animal models including the elevated plus maze, fear conditioning, social interaction, and shock-induced foot tapping (Ballard et al, 2001;File et al, 2001;Gentsch et al, 2002;Rupniak et al, 2003;Varty et al, 2002b); and more recently, antidepressant-like effects in the tail suspension test (Varty et al, 2003). Consistent with these reports, genetic deletion of the NK1 receptor in mice resulted in anxiolytic and antidepressant effects in the elevated plus maze, novelty suppressed feeding model and the FST (Santarelli et al, 2001;Rupniak et al, 2001), providing additional support for the hypothesis that the NK1 receptor may be an important target for antidepressant/anxiolytic therapy.…”
Section: Introductionsupporting
confidence: 52%
“…Importantly, we do not know many of the details about the frequently comorbid, intimate, and possibly related nature of de-pression and anxiety, either phenomenologically or psychobiologically. [27][28][29] …”
Section: Psychopharmacological Treatment Of Anxiety and Its Shortcommentioning
confidence: 99%
“…Many new theories and compounds have been proposed, including those based on 5-HT 1A agonists 10 and other specific serotonin-based compounds, 30,31 NK-1 antagonists and other Substance P-related species, 28 neuropeptides (NPY, NPS), 29,32 more specific GABA A agonists, 33,34 CRF antagonists, 35,36 glutamate modulators, and ␤-blockers, 37,38 among others.…”
Section: New Developments In the Pharmacology Of Anxietymentioning
confidence: 99%
“…Examples are NKP-608, which has been shown to have anxiolytic-like and antidepressant-like properties in social interaction and chronic mild stress models (File 2000;Papp et al 2000;Vassout et al 2000), and FK-888 and WIN51,708, which produced anxiolytic-like effects in mouse and rat elevated plus-mazes, respectively (Teixeira et al 1996;Nikolaus et al 1999). Furthermore, research using NK1 receptor knockout mice have shown that the deletion of the NK1 receptor results in a profile of reduced anxietylike behaviors in a number of models including elevated plus-maze, novelty suppressed feeding, and maternal separation-induced vocalizations (Rupniak et al 2000;Santarelli et al 2001). However, in general, preclinical research with NK1 antagonists has, by pharmacological necessity, focused on species such as guinea pig and gerbil.…”
mentioning
confidence: 99%